The prohibition of terrorism under international humanitarian law and international criminal law - Casey-Maslen, Stuart (University of Pretoria, 2024)
Mini Dissertation (LLM (International Humanitarian Law and Human Rights in Military Operations))--University of Pretoria, 2023.